The Prevalence of Multidrug Resistance of Helicobacter pylori and Its Impact on Eradication in Korea from 2017 to 2019: A Single-Center Study - Jae Yong Park; Tae-Seop Shin; Ji Hyun Kim; Hong Jip Yoon; Beom Jin Kim; Jae Gyu Kim (MDPI AG, 2020)
Antimicrobial resistance is one of the major factors determining the efficacy of Helicobacter pylori eradication therapy. This study aimed to estimate the recent prevalence of multidrug resistance of H. pylori and its impact on eradication in Korea. A total of 174 patients were prospectively enrolled at Chung-Ang University Hospital from 2017 to 2019. H. pylori strains were isolated from the gastric body and antrum. The minimum inhibitory concentrations of antibiotics were determined by the serial twofold agar dilution method. Eradication results were reviewed and analyzed in connection with antibiotic resistance. The prevalence of H. pylori infection was 51.7% (90/174). The culture success rate was 77.8% (70/90). The resistance rates for clarithromycin, metronidazole, amoxicillin, tetracycline, levofloxacin, and moxifloxacin were 28.6% (20/70), 27.1% (19/70), 20.0% (14/70), 18.6% (13/70), 42.9% (30/70), and 42.9% (30/70), respectively. The multidrug resistance (resistance to two or more classes of antimicrobials) rate was 42.9% (30/70). Dual resistance to clarithromycin and metronidazole was confirmed in 8.6% (6/70). Eradication with a first-line treatment was successful in 75% (36/48), and those who received second-line treatment all achieved successful eradication. The rate of multidrug resistance is increasing, and standard triple therapy (STT) is no longer an acceptable first-line option for H. pylori eradication in Korea.